ANALISIS ADOPSI INOVASI TEKNOLOGI PERTANIAN BERBASIS PADI DI SUMATERA SELATAN DALAM PERSPEKTIF KOMUNIKASI - Jauhari Efendy; Yanter Hutapea (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2010)
Analysis of Adoption of Agricultural Technology Innovation Rice-based Farming in Sumatra inthe perspective of communications. Assessment Institute of Agricultural Technology (AIAT) South Sumatrahas produced innovative rice-based farming technology in various agroecosystem. However, adoption ratesare still relatively low. Evaluation of four assessments aimed to identify the factors that predominantly affectthe adoption of technological innovation based local-specific farming rice and to know the level of adoption.This activity is carried out in OKI, East OKU and Banyuasin regencies with 67 respondents interviewedin July-September 2007. The results of this assessment showed that the factors that influence the adoption oftechnological innovations such as the level of selective exposure of technology innovation, cosmopolite,triability, complexity of technology and agricultural extension intensity. The average adoption index for thepacket of rice cultivation technology was 50.32%. As many as 93.02% of respondents have positive perceptionsof the researcher-extension AIAT South Sumatra as the communicator in delivering information technology.Most respondents (80%) expressed a desire to obtain agricultural information generated AIAT South Sumatra.Key words: Adoption, innovation, rice, communication Balai Pengkajian Teknologi Pertanian (BPTP) Sumatera Selatan sudah menghasilkan inovasi teknologipertanian berbasis padi di berbagai agroekosistem. Namun tingkat adopsinya masih relatif rendah. Evaluasi terhadapempat pengkajian ini bertujuan untuk mengidentifikasi faktor-faktor yang dominan mempengaruhi proses adopsiinovasi teknologi pertanian spesifik lokasi berbasis padi dan mengetahui tingkat adopsinya. Kegiatan ini dilakukan diKabupaten OKI, OKU Timur dan Banyuasin dengan mewawancarai 67 orang responden pada bulan Juli – September2007. Berdasarkan hasil analisis deskriptif kualitatif diketahui bahwa (1) adopsi inovasi teknologi budidaya tanamanpadi di Sumatera Selatan dipengaruhi oleh tingkat kebutuhan petani terhadap inovasi teknologi, sifat kekosmopolitanpetani, triabilitas dan kompleksitas teknologi dan intensitas pembinaan, (2) indeks adopsi inovasi petani terhadappaket teknologi budidaya padi kondisinya beragam tergantung pada jenis kegiatan, (3) petani di Sumatera Selatanumumnya memberikan apresiasi positif terhadap peneliti-penyuluh BPTP Sumatera Selatan, terlihat dari tingginyaminat petani untuk mendapatkan berbagai media informasi pertanian BPTP Sumatera Selatan, dan (4) temuankajian ini mengindikasikan faktor komunikasi memegang peran utama yang dapat mempengaruhi adopsi teknologi.Kata kunci : Adopsi, inovasi, padi, komunikasi